"Just let us be" discrimination against LGBT students in the Philippines - Thoreson, Ryan Richard 1984- (Human Rights Watch, 2017)
"This report documents the range of abuses against lesbian, gay, bisexual, and transgender (LGBT) students in secondary school. It details widespread bullying and harassment, discriminatory policies and practices, and an absence of supportive resources that undermine the right to education under international law and put LGBT youth at risk"--Publisher's description.